Agama Islam dan Komunikasi Efektif Dalam Konteks Organisasi - Putri Ayu Widyaningrum; Arindanu Arindanu; Yayat Suharyat; Ismail Mubarok; Lusiana Lusiana (Student Scientific Creativity Journal, 2024)
To anticipate market needs for new goods, effective communication is essential. Organizational communication in Islamic education also helps improve school performance. In an Islamic perspective, effective communication is when a message conveyed by a communicator is well received by the communicant. A good leader can make the company a calm and peaceful place. When one party in the organization feels disadvantaged, conflict can arise. This can happen because of differences in opinion, values, and character. In the Qur'an, humans are described as receiving a lesson directly from God, having a real enemy, Satan, and being able to carry a mandate. Leadership that is knowledgeable, strong, trustworthy and devout is very important. The results of this research indicate that effective communication plays an important role in organizations, Islamic education, and leadership. This research also provides an in-depth understanding of how effective communication relates to Islamic religion and organizations. It is hoped that the results of this research can help and improve the quality significantly, to increase the effectiveness of Islamic education and organizations.